Permittivity Measurement of Modified Infinite Samples by a Directional Coupler and a Sliding Load - Misra D.K. (My University, 2025)
A cross coupler and waveguide sliding short technique for measuring the permittivity of an infinite sample is described in this paper. The experimental results obtained for commercially available cement, wheat flour, magnesium oxide, potassium bromide, glycerin, and water are given together with the estimated error. In view of the growing industrial use of microwaves, moisture dependent e-values for cement and wheat flour are also reported. Copyright © 1981 by The Institute of Electrical and Electronics Engineers, Inc.